Land documents in Dār Fūr sultanate (Sudan, 1785–1875): Between memory and archives - George Michael La Rue (Afriques)
From some Sub-Saharan societies, scholars have found early land documents pertaining to old land-tenure systems. For the study of the ḥākūra system in the Dār Fūr sultanate (Sudan), a rare combination of 18th- and 19th-century land documents in Arabic and the memories of oral informants provided a good look into the past. While the documents include sultanic land grants, court cases, and administrative letters, oral informants could provide a fuller social context by identifying the people mentioned, placing them within lineage and political networks, and showing that documents recorded not undisputed facts but the outcomes of multi-generational power struggles over the land. During site visits, oral informants also indicated key features of the land in question. With this broader set of information, the texts could be placed in the contexts of sultanic strategies, ethnic conflicts, personal agency, commercial development, and climatic variation as evidence of and tools in much larger struggles over land. Land documents from other Sub-Saharan societies undoubtedly had similar contextual information, once available from oral sources.